Exploring the Multiple Functions of Sleeping Sites in Northern Pigtailed Macaques (Macaca leonina) - Juan Manuel José-Domínguez (2018)
© 2015, Springer Science+Business Media New York. Sleeping site selection in nonhuman primates may respond to various ecological factors, including predation avoidance, range defense, and foraging efficiency. We studied the sleeping sites used by a group of northern pigtailed macaques on 124 nights to test these hypotheses. The macaques used 57 different sleeping sites, of which 33 were used only once. They rarely used the same site on consecutive nights. These selection patterns are consistent with an antipredatory function, but may also be related to an antipathogenic strategy. Sleeping sites were located principally in the most heavily used areas of the home range and were generally away from areas of intergroup encounters. However, some of the most heavily used sleeping sites were in the area where intergroup encounters occurred, and intergroup encounters at sleeping sites always showed high levels of agonism, indicating possible intergroup competition over sleeping sites. On 77 % of nights, the study group selected the sleeping site nearest to either the last feeding area that day or to the first feeding area used the next morning, suggesting a foraging efficiency strategy. The mean distances from the sleeping site to the last and first feeding area were 227 m and 127 m, respectively, suggesting a multiple central place foraging strategy. The macaques entered sleeping sites a mean of 27 min before sunset and left 24 min after sunrise, and these times varied in line with the seasonal variation, maximizing daily activities. Overall, predator avoidance and food efficiency were the main factors influencing the selection of sleeping sites. Our observations differ from those found in a semiprovisioned group inhabiting the same study site, which used fewer sleeping sites and reused them much more often. This difference highlights the impact anthropogenic activities may have on sleeping site selection and the flexibility of sleeping patterns in a single species. Such flexibility may have helped the tree-to-ground evolutionary transition of sleep habits in primates.